Effectiveness of Warm and Therapy Compress Therapy Murottal Al-Qur'an Against Decline Dysmenorrhea in Eighth Grade Students (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Dysmenorrhea, or menstrual pain, is a common issue among women, with severity ranging from mild to severe. This study investigates the effectiveness of warm compress therapy and murottal Al-Qur'an therapy in alleviating dysmenorrhea among eighth-grade female students at SMPIT Hikmatul Fadhillah Medan in 2024. Using a quantitative approach, this quasi-experimental research employed a two-group posttest-only control design. The study involved 40 female students selected through purposive sampling, divided into two groups: 20 received warm compress therapy, and 20 underwent murottal Al-Qur'an therapy. Data were analyzed using univariate and bivariate methods with the Mann-Whitney test. The findings revealed that warm compress therapy effectively reduced dysmenorrhea pain (p-value = 0.000, p<0.05), as did murottal Al-Qur'an therapy (p-value = 0.001, p<0.05). Furthermore, a significant difference was observed in the effectiveness of the two therapies, with a p-value of 0.001 (p<0.05). In conclusion, both warm compress and murottal Al-Qur'an therapies are effective in reducing dysmenorrhea, but their levels of effectiveness differ significantly. These findings offer valuable insights into alternative methods for managing menstrual pain in adolescents.